Sensitivity of Modeled Soil NOx Emissions to Soil Moisture. Issue 7 (29th March 2023) - Huber, Daniel E.; Steiner, Allison L.; Kort, Eric A.
Abstract: As emissions of nitrogen oxides (NOx) from fossil fuel combustion decrease, the relative contribution of NOx emissions from managed and unmanaged soils (SNOx ) is increasing. Modeling SNOx presents a challenge as it requires proper characterization of emission dynamics in response to environmental conditions. SNOx is often represented using the Berkeley Dalhousie Soil NOx Parameterization (BDSNP), which relies upon static relationships between soil moisture and SNOx for arid and non‐arid lands. However, soil chamber and atmospheric studies have shown that emission characteristics are more dynamic, with peak emissions often occurring at higher soil moisture content. Here, to better capture observational studies, we update BDSNP by creating a dynamic SNOx response to soil moisture based on a normalized soil moisture index. We compare the standard and updated parameterizations over the contiguous United States (U.S.) for 2011–2020 using input soil moisture data from ERA5‐Land, MERRA‐2 and NLDAS2‐Mosaic and evaluate SNOx across these different input drivers as well as between the standard and updated parameterizations. The standard parametrization exhibits strong sensitivity to different input soil moisture products, with annual U.S. SNOx differences of up to 0.28 Tg N yr −1 . In contrast, the updated parameterization provides a robust representation of SNOx with reduced sensitivity to input soil moisture product with differences of at most 0.03 Tg N yr −1 . The updated parameterization simulates a broad increase in SNOx in non‐arid regions, including much of the Eastern U.S., indicating that this region may be more sensitive to climatically‐driven SNOx as anthropogenic NOx emissions continue to decline. Plain Language Summary: Nitrogen oxides (NOx = NO + NO2 ) are reactive nitrogen gases that have a direct negative impact on health and air quality. While most NOx in the United States derives from fossil fuel combustion, a substantial fraction is released into the atmosphere by microbial processes in the soil. One frequently used model parameterization estimates soil NOx emissions from environmental factors including soil moisture, with a spatially constant relationship between soil NOx and soil moisture despite different soil and ecosystem characteristics. We update this model parameterization to produce variable soil moisture‐NOx relationships for different locations based on local soil moisture history. Unlike the standard parameterization where emissions varied greatly with different soil moisture input datasets, the updated parameterization produces similar results regardless of the soil moisture dataset. The revised soil moisture relationship increases modeled soil NOx emissions over much of the intensively managed cropland across the eastern United States, with potential to influence local and regional air quality. Key Points: A soil NOx emissions (SNOx ) parameterization is updated to reflect the dynamic spatial relationships between soil moisture and SNOx The updated parameterization produces consistent SNOx estimates when using different soil moisture products to drive the model Regions of the Eastern United States with intensively managed cropland experience the largest increases in SNOx